Analisis Partisipasi Pinjaman Rumah Tangga pada Lembaga Keuangan Mikro terhadap Tingkat Kesejahteraan - Aprilia, Ariz; Ananda, Rima Restu (Jurnal Ekonomi dan Pembangunan Indonesia, 2018)
This study aims to analyze the effect of household loan participation on microfinance (LKM) on the level of welfare in the form of expenditure for education and health by using IFLS data in 2014. The methods used are Ordinary Least Square (OLS) and Instrumental Variable (IV). The results of the analysis show that households that make loans are proven to have higher levels of education spending, especially for households in urban areas. Meanwhile, the existence of household loans did not have a significant effect on health expenditure. The conclusion of this study is that household loans only affect expenditure for education, especially for urban households.